Amangeldy Aytaly’s “Ultanu” concept and the challenges to national identity in Kazakhstan (Journal of Philosophy Culture and Political Science, 2026)
The current globalization of human culture, the dominance of digital culture, cultural diversity, and information influence have made the issue of national identity particularly relevant. The theoretical substantiation of ways to preserve and revitalize national identity is one of the main tasks of the social and human sciences. Although Kazakhstan is an independent state, it has not yet fully overcome post-colonial challenges such as the weakening of historical memory, linguistic assimilation, and the fading of spiritual values — all of which pose a serious threat to national unity.In this regard, the concept of “Ultanu” (“Nation Studies”) developed by scholar, statesman and public figure, Doctor of Philosophy, Professor, and Academician of the Academy of Social Sciences of the Republic of Kazakhstan Amangeldy Aytaly plays an important role. This article examines Aytaly’s ideas about national consciousness, language, historical memory, and spiritual security as theoretical and practical foundations for forming and strengthening national identity. In addition, the cultural significance of his concept is highlighted, and its relevance in the context of modern challenges is substantiated. Particular attention is given to the prevention of national nihilism, the preservation of cultural uniqueness, and the improvement of national policy.The purpose of this article is to analyze the theoretical and practical foundations of preserving and strengthening national identity within the framework of Amangeldy Aytaly’s “Ultanu” concept, as well as to demonstrate the relevance and practical significance of his ideas in contemporary society.Amangeldy Aytaly’s ideas on national consciousness are considered as both a theoretical and practical basis for the formation and preservation of national identity in modern Kazakhstani society. His research contributes to the development of national policy and provides important guidance on the path toward Kazakhstan’s cultural and spiritual renewal.Keywords: nationalization, nation building, interethnic relations, national identity, national consciousness